Criminal law and legal dogmatics - Manrique, María Laura (Revus (Ljubljana), 2017)
The authors expose a challenge that legal dogmatics represents to our legal institutions. Legal dogmatics often claims that it plays a necessary role in identifying legal rules and in solving their indeterminacies. Thus, legal dogmatics is to be viewed as an indispensable complement to legislation. Like legislation, dogmatics also attempts to provide judges with precise guidelines to help them pass the right decisions and avoid the arbitrary ones. Only under this assumption does dogmatics help to make more predictable decisions. However, the problem of dogmatics consists that the search for precision which is to intended to limit the arbitrariness of judicial decisions calls for distinctions that are per se arbitrary ones. In some cases, this arbitrariness results from an indeterminacy generated by vague rules, while in other cases the application of precise rules leads to arbitrariness because officials depart from the reasons that ground them. The challenge of dogmatics is to show that its contribution to rationality can be perceived as an improvement on the legislator's contribution. That is, dogmatics must show why its rules can succeed where legislation inevitably fails for conceptual reasons. The authors of this paper claim the opposite. The application of dogmatic rules has the same conceptual difficulties as the application of legislated rules alone.Moreover, dogmatic solutions often contend with other formal justifications, i.e., reasons which ground legislated rules.
Keywords: authority; criminal rules; kazenska pravila; legal dogmatics; oblastni organ; pravna dogmatika; rule of law; vladavina prava